EVALUATION OF PUBLIC GOODS- CONCESSIONS TO ‘CULTURAL GOODS’ AS ‘GOODS OF INTEREST TO THE REPUBLIC OF CROATIA’ WITH EMPHASIS ON THE PARTICULARITIES OF THESE CONCESSIONS - Boris Ljubanović (Zbornik Radova Pravnog Fakulteta u Splitu, 2009)
In contrast to Croatian law which links concession, above all else to the economic use of public goods on the part of the individual or corporations, the French law and practice link concession to the entrustment of performing public works or to the entrustment of some kind of public service to a private contractor or concessionary. French writers also mention concessionship of the public service. This is behaviour by which the particular public power entrusts a concessionary with administering and managing a certain public service under public control with a reward which in principle is contained within the funds of the users of that service. According to Croatian law, cultural goods which are of interest to the Republic of Croatia also enjoy the state’s special protection. The characteristics of cultural goods, on the basis of expert evaluation, are established by the Ministry for Culture. The ownership of cultural goods can be limited accordingly by law. This can be done in the areas of possession, use and operation of cultural good. In comparison to some other ‘goods of interest to the Republic of Croatia’ concessions to cultural goods have a variety of particularities.